2021
DOI: 10.1002/hpm.3276
|View full text |Cite
|
Sign up to set email alerts
|

Kanban system applications in healthcare services: A literature review

Abstract: Lean Management method has been applied in several fields before its implementation in healthcare area. Among the different techniques associated with Lean, in this paper, we are focused on Kanban system, which is a method that presents several benefits such as inventory holding reduction or improvement of the employees' satisfaction. Our main objective is to carry out a literature review focused on Kanban methodology applied to health care. In this sense, this study can serve as a script to improve hospital m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…A recent review (Lanza-Leon et al. , 2021) of the use of Kanban in healthcare revealed that its application tends to be limited to pharmaceuticals/medication flows (Mouaky et al.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review (Lanza-Leon et al. , 2021) of the use of Kanban in healthcare revealed that its application tends to be limited to pharmaceuticals/medication flows (Mouaky et al.…”
Section: Discussionmentioning
confidence: 99%
“…Kanban is an information system that allows control over the production of products in the time and quantity required in all processes, with multiple benefits such as inventory reduction and improved operator satisfaction [16].…”
Section: Kanbanmentioning
confidence: 99%